2006
DOI: 10.1063/1.2357561
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the factors governing the enhanced photoluminescence brightness of Li-doped Y2O3:Eu thin-film phosphors

Abstract: The authors studied the Li concentration dependence of the internal efficiency and extraction efficiency contributions to the enhanced photoluminescence (PL) brightness of the Li-doped Y2O3:Eu thin films. Experiments conducted with excitation at a wavelength of 254nm showed that adding 20mol% Li2CO3 to conventional Y2O3:Eu thin films improved their PL brightness by a factor of over 7.0. This improvement is attributed to enhanced internal factors (crystallinity, grains, and substitution of interstitial oxygen) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
74
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 18 publications
3
74
0
Order By: Relevance
“…Lowdimensional structures exhibit fascinating behavior and have a multitude of potential applications, such as Li-ion batteries, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] fuel cells, [19][20][21][22][23][24][25][26] nanophosphors, [27][28][29][30][31][32][33] and solar cells. [34][35][36][37][38][39] Semiconductor nanocrystals have attracted much attention due to their unique optical properties, which originate from the quantum-confinement effect. Specifically, the confinement of charge carriers and bandgap engineering can be achieved by changing the size of the semiconductor nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Lowdimensional structures exhibit fascinating behavior and have a multitude of potential applications, such as Li-ion batteries, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] fuel cells, [19][20][21][22][23][24][25][26] nanophosphors, [27][28][29][30][31][32][33] and solar cells. [34][35][36][37][38][39] Semiconductor nanocrystals have attracted much attention due to their unique optical properties, which originate from the quantum-confinement effect. Specifically, the confinement of charge carriers and bandgap engineering can be achieved by changing the size of the semiconductor nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A more reduced symmetry of these sites would then result in the enhanced luminescent properties [33]. Origin of this large enhancement in PL brightness is complex [13,15]. The increase in intensity is due to several effects, such as crystallinity (or increase in the oscillation strength), grain size, nano-agglomerations and the substitution of Li for interstitial oxygen (an increase in the hole concentration).…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, luminescent properties of nanostructured phosphors can be enhanced by the introduction of suitable co-dopant materials to phosphor matrix. It is reported [13][14][15] that even in very small quantities, Li + ions, as co-dopant, can play an important role in increasing the luminescent efficiency of bulk phosphors. Techniques like sputtering, pulsed laser deposition, vacuum evaporation, electron beam evaporation, spray pyrolysis and chemical deposition [11,[16][17][18][19][20] have been used for the preparation of yttrium based oxide thin films.…”
Section: Introductionmentioning
confidence: 99%
“…In 1996 Yeh and Su [2] showed that the mixing of LiF in Gd 2 O 3 :Eu 3+ phosphor increases its thermo-and photo-luminescence sensitivities. After that, the luminescence enhancement by Li substitution has been reported in zinc compounds (ZnO:Dy 3+ ) [3], polycrystalline garnet (Y 3 Al 5 O 12 :Tm 3+ ) [4], microcrystalline compounds (Gd 2 O 3 :Eu 3+ [5] and Y 2Àx Gd x O 3 :Eu 3+ [6]), nanosized Y 2 O 3 :Eu 3+ phosphors [7], and thin film phosphors (Y 2 O 3 :Eu 3+ [1], Gd 2 O 3 :Eu 3+ [8], and YVO 4 :Eu 3+ [9]). It has been suggested that the luminescence enhancement by Li doping is due to the improved crystallinity, enhanced surface morphology, increase in surface roughness, reduction in internal reflection [5,6,8], and decrease in interstitial oxygen and increase in hole concentrations [10] by means of X-ray diffraction (XRD), scanning emission microscope (SEM), atomic force microscope (AFM), and transmission electron micrograph (TEM).…”
Section: Introductionmentioning
confidence: 98%
“…The luminescence efficiency of thin films, however, is lower than that of powder phosphors due to the poor light extraction efficiency and poor internal efficiency [1]. One of the most important requirements for the phosphors is a sufficient luminescence efficiency which is governed by numerous factors in the materials.…”
Section: Introductionmentioning
confidence: 99%